Immunotoxic effects of cyclophosphamide and cyclosporine in the dog. (March 2013) - Legrand, Jean-Jacques; Bouchez, Caroline; Mimouni, Cécile; N'Guyen, Armelle; Bouchard, Johanne; Ameller, Thibault; Descotes, Jacques
<x xml:space="preserve">Abstract</x> Limited non-clinical immunotoxicity data are available in the dog, although this is a major non-rodent species in regulatory safety studies. The present study aimed to test whether widely accepted immunotoxicity endpoints including lymphocyte subset immunophenotyping, the anti-KLH TDAR assay, and histological examination of the main lymphoid organs were reliable to detect immunosuppression induced by cyclosporine and cyclophosphamide in dogs and could, therefore, be used for non-clinical immunotoxicity evaluation in this species. Male and female Beagle dogs were treated orally from Day 1 for 4 weeks with 25 mg/kg cyclosporine daily, or with 2 mg/kg cyclophosphamide on 4 consecutive days each week, or the same volume of drinking water daily. Blood samples were withdrawn pre-test and on Days 11, 18, and 23 to measure standard hematology parameters and analyze lymphocyte subsets. All animals received an intramuscular injection of 5 mg KLH on Day 11. Sandwich ELISA assays were used to quantify anti-KLH IgM and anti-KLH IgG levels in blood samples taken pre-test, on Days 18 and 23, and pre-test, on Days 23 and 28, respectively. At the end of the treatment period, all animals were submitted to histological examination of lymphoid organs, liver, and kidneys. No signs of marked toxicity were observed. No changes in lymphocyte subsets, but markedly decreased primary anti-KLH IgM and IgG responses, and a slightly-to-markedly increased cortex/medulla ratio in the thymus were observed in cyclosporine-treated dogs. Lower total WBC counts correlating with lower total and B-lymphocyte subset and decreased germinal center development in mesenteric lymph nodes, but no changes in primary anti-KLH IgM and IgG responses were observed in cyclophosphamide-treated dogs. These results demonstrate that widely accepted immunotoxicity endpoints can adequately detect the effects of known immunosuppressive drugs in the dog and support the conclusion that it is a relevant animal species for immunotoxicity evaluation.